Early cretaceous ridge subduction in the Shandong Peninsula, Eastern China, indicated by Laoshan A-type granite - Li, Jie; Li, He; Li, Congying; Song, Mingchun; Jiang, Mengyao; Yuan, Shuai; Zhang, Lipeng (Frontiers in Earth Science, 2023)
Early Cretaceous A-type granites are widespread in the Shandong Peninsula, which can be used to elucidate the tectonic evolution of the eastern China and the destruction of the North China Craton. However, their genesis is still controversial. Several competing models, ranging from slab break-off, postorogenic extension, foundering of the lower crust and ridge subduction, were proposed. Here, we report zircon U–Pb ages, whole-rock and apatite geochemical compositions of the Laoshan granite and discuss its tectonic implications. The Laoshan granite has typical characteristics of A-type granite with high FeOT/(FeOT + MgO) ratios (0.90-0.97) and 10000*Ga/Al ratios (2.70-3.36) and high total alkali (Na2O + K2O: 7.95-8.70 wt.%) contents and Zr+Nb+Ce+Y (most >350 ppm) concentrations. The Laoshan granite is further classified as A1-type based on the Yb/Ta-Y/Nb and Ce/Nb-Y/Nb diagrams and the Nb-Y-3Ga and Nb-Y-Ce triangular discriminant diagrams. Zircon U–Pb dating of two Laoshan granite samples yielded emplacement ages of 117.8 ± 1.0 Ma and 120.1 ± 1.3 Ma, respectively. The oxygen fugacity of the Laoshan granite magma is low, as indicated by zircon Ce4+/Ce3+ ratios (most <300). The crystallization temperature of zircon varies significantly, ranging from 652 to 830 °C. The apatite compositions show that the Laoshan granite has high F (2.09-2.72 wt.%) and low Cl (0.01-0.09 wt.%) contents, consistent with influence by fluid released from the decomposition of phengite. Apatite rare earth elements show that mantle sources are also involved in Laoshan A-type granite. Combined previous studies of A-type granitic plutons in the Shandong Province and the Lower Yangtze River belt with the drifting history of the Pacific plate, we propose that the flat subduction of the spreading ridge between the Pacific and the Izanagi plates was responsible for the formation of Laoshan A-type granite.